Development of a core outcome set for open lower limb fracture: what core outcomes should be measured?. Issue 4 (20th April 2023) - Aquilina, Alexander L.; Claireaux, Henry; Aquilina, Christian O.; Tutton, Elizabeth; Fitzpatrick, Ray; Costa, Matthew L.; Griffin, Xavier L.
Abstract : Aims: Open lower limb fracture is life-changing, resulting in substantial morbidity and resource demand, while inconsistent outcome-reporting hampers systematic review and meta-analysis. A core outcome set establishes consensus among key stakeholders for the recommendation of a minimum set of outcomes. This study aims to define a core outcome set for adult open lower limb fracture. Methods: Candidate outcomes were identified from a previously published systematic review and a secondary thematic analysis of 25 patient interviews exploring the lived experience of recovery from open lower limb fracture. Outcomes were categorized and sequentially refined using healthcare professional and patient structured discussion groups. Consensus methods included a multi-stakeholder two-round online Delphi survey and a consensus meeting attended by a purposive sample of stakeholders, facilitated discussion, and voting using a nominal group technique. Results: Thematic analysis and systematic review identified 121 unique outcomes, reduced to 68 outcomes following structured discussion groups. Outcomes were presented to 136 participants who completed a two-round online Delphi survey. The Delphi survey resulted in 11 outcomes identified as consensus 'in' only. All outcomes were discussed at a consensus meeting attended by 15 patients, 14 healthcare professionals, 11 researchers, and one patient-carer. Consensus was achieved for a four-core outcome set: 'Walking, gait and mobility', 'Being able to return to life roles', 'Pain or discomfort', and 'Quality of life'. Conclusion: This study used robust consensus methods to establish a core outcome set that should be measured in all future research studies and audits of clinical practice without precluding the measurement of additional outcomes. Cite this article: Bone Joint Res  2023;12(4):294–305.